Analisis Pengelolaan Donasi Digital dalam Perspektif Akuntansi Islam pada Platform Crowdfunding Syariah - St Amirah Hasbir; Dhea Artika; Fadil Maulana; Masyhuri Masyhuri (Indo Publishing, 2026)
The rapid development of digital technology has encouraged the emergence of sharia crowdfunding platforms as a modern medium for collecting and distributing social funds. Digital donation systems provide convenience, efficiency, and increase public participation in Islamic philanthropic activities. However, the growing use of digital platforms also raises various issues related to transparency, accountability, and compliance with Islamic accounting principles. This study aims to analyze the management of digital donations from the perspective of Islamic accounting on sharia crowdfunding platforms. The research uses a descriptive qualitative method with a literature study approach by examining journals, books, regulations, and previous studies related to Islamic accounting and digital donation management. The findings indicate that sharia crowdfunding platforms have generally implemented the principles of transparency and accountability in fund management, although challenges still remain regarding supervision, financial reporting standardization, and public trust. From the perspective of Islamic accounting, digital donation management must prioritize honesty, justice, trustworthiness, and compliance with Islamic principles. Therefore, strengthening sharia supervision, improving digital security systems, and increasing public literacy regarding sharia financial technology are essential to optimize digital donation management on sharia crowdfunding platforms.